Anaplasmose bovina: parâmetros clínicos e de patologia clínica em bezerros infectados experimentalmente.: parâmetros clínicos e de patologia clínica em bezerros infectados experimentalmente. - Leonardo Costa Tavares Coelho (2007)
The clinico-pathological findings of Anaplasmosis, were evaluated in five Holstein calves, with 90 to 120 days old, inoculated with A. marginale. The mean incubation period was 13 days, the mean patent period lasts for 14 days and the mean convalescent stage 10 days. The clinical, hematological, biochemical, acid-base, electrolyte and urinary disturbances were evaluated during the patent period. The calves develop a normocitic, normochromic anemia that turns to macrocitic, normochromic in convalescent period. The evaluation of ion and electrolytes concentrations revealed decreased Na+, Cl- and HCO3- at the peak of anemic crisis. The analysis of blood gases showed the occurrence of a totally compensated metabolic acidosis in survivor animals, with an little increased blood pH and a reduced pCO2 and HCO3- concentration. In fatal cases an uncompensated metabolic acidosis occurs, with drastic reductions in blood pH, HCO3-, pCO2 and BE values and a great increase in AG. Results showed increased plasma nitrogen urea body (BUN) and decreased glucoses and hemoglobin concentrations. It was noticed a strong negative correlation between the hematocrit values and the Na+, Cl- and HCO3- concentrations leading the development of an equation, by a linear regression analysis, to predict the concentrations of Na+, Cl- and HCO3- using the hematocrit values, that could be used for the development of new treatment strategies.